"Emerging role of Novel Seminal Plasma Bio-markers in Male Infertility: A Review". (October 2020) - Kumar, Naina; Singh, Namit Kant
Abstract: Male infertility has emerged as an important cause of infertility worldwide. There are many factors affecting male fertility and research is going on to know impact of various factors on sperm functions. Semen analysis is gold standard diagnostic test for male infertility, but it is crude method for estimation of male infertility as seminal composition gets affected by environmental factors, infections, other pathologies, hence, results of semen analysis either becomes normal/ambiguous, leading to failure of diagnosis and delayed treatment. Hence, with need of newer, better tests for assessing male factor infertility, seminal plasma is being tested for biomarkers. Seminal plasma is considered gold mine for male fertility as it contains molecules from male reproductive glands which play important role in sperm function. Study of seminal plasma molecules can give an idea about sperm concentration, motility, morphology and cause of infertility and can serve as biomarkers for male infertility. Present review briefs on some of these novel seminal plasma biomarkers which may play significant role in male fertility and can be used in future for better identification, assessment of infertile males. Methodology: Literature from 1985 to 2019 was searched from various databases including PUBMED, SCOPUS, Google Scholar on seminal plasma biomarkers using keywords: "seminal plasma protein biomarkers", "novel seminal plasma markers and male infertility", "hormones in seminal plasma and male infertility", "oxidative stress and male infertility", "Reactive Oxygen Species and sperm DNA", "immunoinfertility". Inclusion criteria: All full length original or review articles or abstracts on seminal plasma markers and male infertility published in English language in various peer-reviewed journals were considered. Exclusion criteria: Articles published in languages other than English were excluded from the study. Results: Seminal plasma is a big reservoir of molecules derived from the various male reproductive glands which can be used as potential biomarkers of male fertility. Conclusion: Hence, seminal plasma biomarkers can be used in future for better assessment of male factor infertility, its causes and may play an important role in management of male factor infertility.